In vivo alterations in the gonadotropin-releasing hormone pulse generator and the secretion and clearance of luteinizing hormone in the uremic castrate Rat - Schaefer, Franz; Daschner, Markus; Veldhuis, Johannes D.; Oh, Jun; Qadri, Fatimunnisa; Schärer, Karl (Neuroendocrinology, 1994)
To investigate the mechanisms subserving the reported alterations in the pulsatile release of LH in uremia, we simultaneously studied endogenous accumulation of GnRH in the pituitary gland and the secretion and clearance of LH in vivo in experimentally uremic, orchidectomized rats. The temporal pattern of GnRH secretion was assessed by intrapituitary microdialysis, the dynamics of plasma LH by continuous exchange transfusion. Studies were performed in rats rendered uremic by subtotal nephrectomy (n = 8) and control rats which were either fed ad libitum (n = 8) or pair-fed with the uremic animals (n = 8). Blood samples were obtained at 5-min and microdialysate samples at 10-min intervals over a period of 270 min. The pulsatile secretory characteristics of GnRH and LH and the half-life of plasma LH were estimated by multiple-parameter deconvolution analysis. The temporal relationship between the hormone concentrations and between the secretory events of GnRH and LH was assessed by cross-correlation analysis and hypergeometric coincidence analysis. We observed that: (1) the estimated half-life of plasma LH was prolonged in uremic (59 ± 10 min) rats compared to ad libitum-fed (17 ± 3 min, p = 0.014) and pair-fed controls (19 ± 3 min, p = 0.025); (2) the LH production rate was decreased in uremic animals (18 ± 5 ng/ml·270 min) compared to ad libitum-fed (37 ± 4 ng/ml-270 min, p = 0.002) and pair-fed controls (48 ± 9 ng/ml·270 min, p = 0.0006); (3) the reduction of LH secretion rate in the uremic animals was accounted for by a decrease in detectable LH pulse frequency (2.1 ± 0.2 peaks/h) compared to ad libitum-fed (3.1 ± 0.1 peaks/h, p = 0.01) and pair-fed controls (2.8 ± 0.2 peaks/h, p = 0.06) and a diminished mass of hormone released per burst (uremic 1.8 ± 0.2 ng/ml, ad libitum-fed 2.6 ± 0.3 ng/ml, p = 0.05, pair-fed 3.8 ± 0.8 ng/ml, p = 0.025); (4) the secretion rate of GnRH was reduced to a similar degree in uremic rats (180 ± 15 pg/tube -270 min, p = 0.04) and pair-fed controls (170 ± 26 pg/tube-270 min, p = 0.04) compared to ad libitum-fed controls (270 ± 36 pg/ tube-270 min). In contrast to the reduced number of detectable LH secretory events, the frequency of GnRH secretory peaks in uremic rats was not different from ad libitum-fed and pair-fed controls. The reduced GnRH secretion rate in uremic and pairfed animals was entirely attributable to a decrease mass of GnRH released per burst (uremic 18+ 1.5, p = 0.06; pair-fed 17 ± 2.2, p = 0.046; ad libitum-fed 27 + 3.6 pg/tube); (5) the number of coincident GnRH and LH secretory events exceeded the rate expected by chance alone (p < 10-5) in all three groups of animals. Cross-correlation analysis showed the highest concordance between GnRH and LH for LH concentrations lagging GnRH by 0-5 min. Eighty-two percent of the GnRH impulses observed in the control groups, but only 62% in the uremic group coincided within + 5 min with a GnRH impulse. In conclusion, our findings indicate that reduced metabolic clearance masks pituitary hyposecretion of LH in uremic rats. Decreased LH production results from a reduction in GnRH impulse strength and altered hypothalamo-pituitary signal transduction. The former finding may be related to mild malnutrition and/or paracrine autoregulation, while the latter appears to be uremia-specific.
Published online: April 08, 2008
Gesehen am 15.12.2020